Strategi Pendidikan Agama Kristen Dalam Menanamkan Sikap Moderasi Beragama di Sekolah Tinggi Teologi - Novi Kristiani Tahalele; Seli Antonia Tagu Sunga; Bazahati Laia; Yoel Triyanto; Wahyu A. Rini (Sekolah Tinggi Teologi Ekumene Jakarta., 2024)
Religious moderation is an attitude and way of thinking that upholds the values of justice, balance, straightness, tolerance, priority, civility, and creativity in understanding and practicing religious teachings. Religious moderation is considered important and is one of the values that must be instilled in all students in Indonesia, including those at the Jakarta School of Ecumenical Theology. Students are seen as crucial in learning the value of religious moderation, especially in light of recent issues arising from political conflicts between Israel and Palestine, which are often linked to religion. This has become a sensitive issue that may fuel conflicts among religious communities, emphasizing the need for the frequent incorporation of moderation education. The purpose of this research is to understand the implementation of Christian Religious Education strategies in instilling a stance of religious moderation at the Jakarta School of Ecumenical Theology. The research method employed is qualitative, utilizing observation and interview techniques. The Jakarta School of Ecumenical Theology has already instilled the values of religious moderation in lectures conducted during a single session. This serves as a specific strategy within Christian Religious Education to instill the values of religious moderation, aiming to create a harmonious and peaceful environment.